2021
DOI: 10.1177/1048371321996292
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Music Online: Using Microsoft PowerPoint to Create Prerecorded Lessons

Abstract: The COVID-19 pandemic has resulted in many schools temporarily moving to online learning. For some general music teachers, this involves prerecording lessons. This column discusses how general music teachers can create prerecorded lessons using Microsoft PowerPoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Sean Beirnes and Clint Randles (Beirnes & Randles, 2022) found that teachers use digital tools to enhance students' experiences and enable them to be creative, which was not possible before the pandemic. Furthermore, the digital tools provide the teacher with the opportunity to better understand and support students during learning (Duncan, 2021), offer pre-recorded music lessons with interactive elements (Norman, 2021b), and help to assess students' level of understanding and facilitate feedback (Norman, 2021a). Digital tools and platforms help music teachers to share material, communicate, exchange messages and keep track of all work done (Biasutti et al, 2021).…”
Section: Teaching Modes and Digital Tools That Support Music Educationmentioning
confidence: 99%
“…Sean Beirnes and Clint Randles (Beirnes & Randles, 2022) found that teachers use digital tools to enhance students' experiences and enable them to be creative, which was not possible before the pandemic. Furthermore, the digital tools provide the teacher with the opportunity to better understand and support students during learning (Duncan, 2021), offer pre-recorded music lessons with interactive elements (Norman, 2021b), and help to assess students' level of understanding and facilitate feedback (Norman, 2021a). Digital tools and platforms help music teachers to share material, communicate, exchange messages and keep track of all work done (Biasutti et al, 2021).…”
Section: Teaching Modes and Digital Tools That Support Music Educationmentioning
confidence: 99%
“…This is beneficial for those families who have limited access to electronic devices and require greater flexibility. Last, with the technology available today, it is quite manageable to create engaging and interactive prerecorded lesson videos (see Norman, 2021aNorman, , 2021b. Students can work through these lessons at their own pace, as they have the option of pausing and rewinding the video, which is not possible during a live lesson.…”
Section: Benefits and Disadvantagesmentioning
confidence: 99%
“…In two previous columns, I describe how general music teachers can create prerecorded lesson videos using Microsoft Powerpoint (Norman, 2021a) and share these online using Microsoft Stream and Forms (Norman, 2021b). My current experience of online learning significantly draws on the content described in Norman (2021a), as I have continued to prerecord general music lessons using Microsoft PowerPoint. However, I have not been using Microsoft Stream and Forms, as the school in which I teach has subscriptions to products that provide similar functions.…”
mentioning
confidence: 99%
“…The use of online interactive teaching mode in university music teaching under the background of informationization 3 lessons is as effective as or better than traditional instruction and that the method can meet the individual needs of different students and save time and effort [18].…”
Section: Introductionmentioning
confidence: 99%